Rapid detection of authenticity and adulteration of walnut oil by FTIR and fluorescence spectroscopy: A comparative study. (15th August 2015) - Li, Bingning; Wang, Haixia; Zhao, Qiaojiao; Ouyang, Jie; Wu, Yanwen
Highlights: FTIR and chemometrics were used to detect the authenticity of walnut oil. FTIR and chemometrics were used to detect the adulteration of walnut oil. The classification limit of soybean oil adulterated in walnut oil by FTIR was 10%. Fluorescence spectroscopy was used to detect the adulteration of walnut oil. The classification limit detected by fluorescence spectroscopy was less than 5%. Abstract: Fourier transform infrared (FTIR) and fluorescence spectroscopy combined with soft independent modeling of class analogies (SIMCA) and partial least square (PLS) were used to detect the authenticity of walnut oil and adulteration amount of soybean oil in walnut oil. A SIMCA model of FTIR spectra could differentiate walnut oil and other oils into separate categories; the classification limit of soybean oil in walnut oil was 10%. Fluorescence spectroscopy could differentiate oil composition by the peak position and intensity of emission spectrum without multivariate analysis. The classification limit of soybean oil adulterated in walnut oil by fluorescence spectroscopy was below 5%. The deviation of the prediction model for fluorescence spectra was lower than that for FTIR spectra. Fluorescence spectroscopy was more applicable than FTIR in the adulteration detection of walnut oil, both from the determination limit and prediction deviation.